2003
DOI: 10.1046/j.1460-9568.2003.02937.x
|View full text |Cite
|
Sign up to set email alerts
|

Attention capture by auditory significant stimuli: semantic analysis follows attention switching

Abstract: Event-related potentials (ERPs) were recorded from the scalp to investigate a long-standing controversy in auditory attention research, namely when the 'breakthrough of the unattended' takes place in the human brain. Nine subjects classified visual stimuli appearing 300 ms after task-irrelevant standard tones (80%, i.e. P = 0.8) or novel sounds (20%, i.e. P = 0.2) into odd/even categories. After the recording session, subjects scored the novel sounds as to whether they had any particular meaning (identifiable)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
127
3
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(146 citation statements)
references
References 27 publications
(44 reference statements)
12
127
3
4
Order By: Relevance
“…Typically, the N400 is not elicited when sounds are processed outside the focus of attention (cf. Mecklinger et al, 1997;Escera et al, 2003). Correspondingly, the present data only indicate a semantic analysis of the familiar stimulus after a physical deviance attracted attention to the sounds.…”
Section: Location-deviant Processing For the Familiar And The Unfamilcontrasting
confidence: 87%
See 2 more Smart Citations
“…Typically, the N400 is not elicited when sounds are processed outside the focus of attention (cf. Mecklinger et al, 1997;Escera et al, 2003). Correspondingly, the present data only indicate a semantic analysis of the familiar stimulus after a physical deviance attracted attention to the sounds.…”
Section: Location-deviant Processing For the Familiar And The Unfamilcontrasting
confidence: 87%
“…Whereas the reviewed effects were observed when sounds were ignored, familiarity effects for complex environmental sounds were so far only addressed for attended sounds (e.g., Lenz et al, 2007;van Petten and Rheinfelder, 1995) or attention-capturing, ''novel" sounds (e.g., Escera et al, 2003;Mecklinger et al, 1997). For the first time, the present study compared the processing of a familiar and an unfamiliar environmental sound when sounds were presented as regular, non-deviant items outside the focus of attention.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, more recent research has found an enhancement of the MMN amplitude when stimuli are attended [24]. This enhancement of amplitude was found to be associated to frontal generators of the MMN, namely IFG, but not to temporal generators of the MMN, namely STG [25,26].…”
Section: Gaining Mismatch Negativity! Improving Auditory Phoneme Discmentioning
confidence: 84%
“…1) implemented in previous studies (Escera et al, 1998(Escera et al, , 2003. In each run, a single digit number (2, 3, 4, 5, 6, 7, 8, or 9) appeared for 200 ms in the center of the screen, with a 3.3 s interstimulus interval.…”
Section: Experimental Taskmentioning
confidence: 99%